Effective Reduction in High Ethanol Drinking by Semisynthetic Tetracycline Derivatives. (14th November 2016) - Syapin, Peter J.; Martinez, Joseph M.; Curtis, David C.; Marquardt, Patrick C.; Allison, Clayton L.; Groot, Jessica A.; Baby, Carol; Al‐Hasan, Yazan M.; Segura‐Ulate, Ismael; Scheible, Matthew J.; Nicholson, Katy T.; Redondo, Jose Luis; et al.
Abstract : Background: New pharmacotherapies to treat alcohol use disorders (AUD) are needed. Given the complex nature of AUD, there likely exist multiple novel drug targets. We, and others, have shown that the tetracycline drugs, minocycline and doxycycline, reduced ethanol (EtOH) drinking in mice. To test the hypothesis that suppression of high EtOH consumption is a general property of tetracyclines, we screened several derivatives for antidrinking activity using the Drinking‐In‐the‐Dark (DID) paradigm. Active drugs were studied further using the dose–response relationship. Methods: Adult female and male C57BL/6J mice were singly housed and the DID paradigm was performed using 20% EtOH over a 4‐day period. Mice were administered a tetracycline or its vehicle 20 hours prior to drinking. Water and EtOH consumption was measured daily. Body weight was measured at the start of drug injections and after the final day of the experiment. Blood was collected for EtOH content measurement immediately following the final bout of drinking. Results: Seven tetracyclines were tested at a 50 mg/kg dose. Only minocycline and tigecycline significantly reduced EtOH drinking, and doxycycline showed a strong effect size trend toward reduced drinking. Subsequent studies with these 3 drugs revealed a dose‐dependent decrease in EtOH consumption for both female and male mice, with sex differences in efficacy. Minocycline and doxycycline reduced water intake at higher doses, although to a lesser degree than their effects on EtOH drinking. Tigecycline did not negatively affect water intake. The rank order of potency for reduction in EtOH consumption was minocycline > doxycycline > tigecycline, indicating efficacy was not strictly related to their partition coefficients or distribution constants. Conclusions: Due to its effectiveness in reducing high EtOH consumption coupled without an effect on water intake, tigecycline was found to be the most promising lead tetracycline compound for further study toward the development of a new pharmacotherapy for the treatment of AUD. Abstract : Of 7 tetracycline class drugs tested using the Drinking in the Dark model, tigecycline was most effective in reducing binge alcohol consumption without reducing overall fluid consumption. However, the drug was more efficacious in male than female C57BL/6J mice.